2008
DOI: 10.1002/cne.21638
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and vasopressin receptor distributions in a solitary and a social species of tuco‐tuco (Ctenomys haigi and Ctenomys sociabilis)

Abstract: The neuropeptides oxytocin and vasopressin and their receptors have been implicated in elements of mammalian social behavior such as attachment to mates and offspring, but their potential role in mediating other types of social relationships remains largely unknown. We performed receptor autoradiography to assess whether forebrain oxytocin receptor (OTR) or vasopressin V1a receptor (V1aR) distributions differed with social structure in two closely related and ecologically similar species of South American rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 66 publications
5
123
1
Order By: Relevance
“…Oxytocin-neurophysin-immunoreactive processes within the nucleus accumbens are extremely sparse in Cape mole-rats, but abundant in naked mole-rats; the latter finding is consistent with the results of a recent study on naked mole-rats by Rosen et al (2008). Meadow voles, mice, rats, and guinea pigs also show oxytocin-containing processes in the nucleus accumbens (Castel and Morris, 1988; Dubois-Dauphin et al, 1989; Ross et al, 2009a), but, unlike naked mole-rats and monogamous voles, they have low or undetectable OTR binding at this site (Insel and Shapiro, 1992a;Tribollet et al, 1992;Olazabal and Young 2006;Beery et al, 2008).…”
Section: Nucleus Accumbenssupporting
confidence: 84%
“…Oxytocin-neurophysin-immunoreactive processes within the nucleus accumbens are extremely sparse in Cape mole-rats, but abundant in naked mole-rats; the latter finding is consistent with the results of a recent study on naked mole-rats by Rosen et al (2008). Meadow voles, mice, rats, and guinea pigs also show oxytocin-containing processes in the nucleus accumbens (Castel and Morris, 1988; Dubois-Dauphin et al, 1989; Ross et al, 2009a), but, unlike naked mole-rats and monogamous voles, they have low or undetectable OTR binding at this site (Insel and Shapiro, 1992a;Tribollet et al, 1992;Olazabal and Young 2006;Beery et al, 2008).…”
Section: Nucleus Accumbenssupporting
confidence: 84%
“…As far as we are aware, a similarly dense innervation of the accumbens has not been reported for any other rodent species, although there is some Oxt innervation of this region in prairie voles (Lim et al, 2004). Oxt receptors also are absent or are expressed at low levels in the accumbens of most rodents (reviewed in Beery et al, 2008). An important exception is again the prairie vole, where Oxt receptors in the nucleus accumbens, are relatively abundant, and are thought to contribute to parental behaviors and a monogamous social structure (Insel and Shapiro, 1992;Liu and Wang, 2003).…”
Section: Discussionmentioning
confidence: 82%
“…A recent study on another social species, Ansell's mole-rat Fukomys anselli [34], examined the distribution of OXT and AVP immunoreactive neurons, but not receptor distributions, thus preventing a full comparison across the family. Looking beyond the Bathyergidae at other Hystricognath rodents in the family Ctenomyidae, Beery et al [35] also found marked differences in OXT and V1a receptor distributions between a social and a solitary dwelling species of tuco-tuco (Ctenomys sociabilis and Ctenomys haigi, respectively). However, they exhibited a pattern of nucleus accumbens OXT and ventral pallidum V1a receptor binding that was different from that associated with the formation of opposite-sex pair bonds in voles; in particular, binding was completely absent in the nucleus accumbens.…”
Section: Proximate Factors (A) Neurobiology Of Social Behaviourmentioning
confidence: 99%